Motivasi, komunikasi persuasif, dan pelatihan manajemen risiko kebidanan untuk meningkatkan profesionalisme bidan dalam mencegah kematian ibu - Ai N Zannah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2018)
Obstetric complication is the direct cause of maternal mortality which could be prevented by improving the professionalism of midwives manifested through competence and ethical training. This study aimed to analyze the effect of motivational training, persuasive communication, and obstetric risk management to midwives' professionalism in order to prevent maternal mortality. The approach of quasi-experiment pre-posttest design with control groups were administered in this study. A total of 60 midwives from health service centers in Tasikmalaya Regency area were chosen as subjects by consecutive sampling, and divided into treatment and control groups. Professionalism consisting of ethics and competence was measured by using a questionnaire and checklists. Data analysis was conducted by Simple Linear Regression Test, Fisher’s Exact, and T-Test. The findings of this study showed the increase in professionalism (ethics and competence) midwives after training, with an increase of 28.6% (17.57%; 32.84%; p<0,001). The effect of training on professionalism was 65%, and the trained midwives were 2.89 times more likely to have higher professionalism than those who did not attend the training. The training on motivation, persuasive communication, and obstetrics risk management can be an intervention to improve the professionalism of midwives that will impact on efforts to prevent maternal deaths